Optimizing Agricultural Cultivation, Fisheries, Processed Products and Marketing in Mugarsari Urban Village of Tasikmalaya City through Innovative and Sustainable Approaches - Suhardjadinata, Suhardjadinata; Juhaeni, Ade Hilman; Benatar, Gilang Vaza; Salam, Rudhiana (PT FORMOSA CENDEKIA GLOBAL, 2024)
The optimalisation of agricultural cultivation, fisheries, processed products, and marketing in Mugarsari urban village of Tasikmalaya city aims to increase productivity, quality, and marketability of agricultural and fishery products in Mugarsari village through innovative and sustainable approaches. Innovative approaches include the application of new technologies and methods in agricultural cultivation and fisheries, while sustainable approaches involve the use of environmentally friendly technologies and resource management. The results of this optimization process are expected to be increased productivity and quality of agricultural and fishery products in Mugarsari village, as well as increased income for local farmers and fishers through improved marketing. Additionally, this optimization process is expected to have a positive impact on the environment through the application of environmentally friendly technologies and resource management.